A Study on the Mineralization of the Woxi Au–Sb–W Deposit, Western Hunan, China. Issue 1 (January 2015) - Liang, Yi; Wang, Guogang; Liu, Shengyou; Sun, Yuzhen; Huang, Yonggang; Hoshino, Kenichi
Abstract The Woxi Au–Sb–W deposit in the western Hunan Province, China, is of hydrothermal vein type characterized by a rare mineral assemblage of stibnite, scheelite and native gold, of which gold fineness ranges from 998.6 to 1000. The mineralization sequence observed in the deposit is, from early to late, coarse‐grained pyrite – scheelite – stibnite – Pb–Sb–S minerals – sphalerite (+ cubanite) – fine‐grained pyrite. Native gold may have precipitated with scheelte. Microthermometric and LA–ICP–MS analyses of fluid inclusions in scheelite, quartz associated with scheelite and stibnite and barren quartz clarified that there may be at least three types of hydrothermal fluids during the vein formation in the Woxi deposit. Scheelite and native gold precipitated from the fluid of high temperature and salinity with high concentrations of metal elements, followed by stibnite precipitation. The later fluid of the highest temperature and salinity with low concentrations of the elements yielded the sphalerite mineralization. The latest fluid of low temperature and salinity with low concentrations of the elements is observed mainly in barren quartz. The remarkably high Au/Ag concentration ratios determined in the fluid inclusions in scheelite might be the reason for the extremely high gold fineness of native gold.